Biomechanical characterization dismount from balance beam on the basis of the analysis of key elements of sports equipment - Potop, V. A.; Rafal, G.; Boloban, V. N.; Otsupok A. P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose. Biomechanical analysis of sports performance technology with balance beam dismount.